Scope review protocol for mapping medication safety patients in the hospital context (Research, Society and Development, 2023)
This is a scoping review protocol on medication safety for hospitalized elderly people. The objective will be to map the scientific evidence available in the literature on medication safety for the elderly in the hospital context, from drug interactions/adverse events in individuals aged 60 or over using medication. A search will be carried out for literature published in English, Portuguese or Spanish in the PubMed, VHL – LILACS, MEDLINE, IBECS, BDENF and CINAHL databases, with descriptions established by MESH and DECS. Two authors will review the title, abstract and full texts for eligibility. PRISMA recommendations will be used to extract data from the reviewed studies, according to the following criteria: studies involving hospitalized elderly people (age ≥ 60 years); literature reporting vulnerabilities due to the use of medications; studies carried out in hospitals; primary studies; studies published in English, Portuguese or Spanish. The extracted data will be tabulated, along with a narrative summary providing a comprehensive analysis of medication safety in hospitalized elderly people.